UJI AKTIVITAS ANTIOKSIDAN EKSTRAK TELUR KEONG MAS (Pomacea canaliculata) DENGAN METODE DPPH (2,2-DIFENIL-1-PIKRILHIDRAZIL) MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Eva Kholifah (Parapemikir : Jurnal Ilmiah Farmasi, 2023)
Antioxidant are compound that could donate one or more electron to free radical to inhibit free radical reaction. One of the mollusc that has the potential to be an antioxidant is the egg of the gold snail (Pomacea canaliculata). The purpose of this study was to determine the antioxidant activity of gold snail egg. Testing of antioxidant activity was carried out by the DPPH (2,2-diphenyl-1-picrilhydrazyl) method. Gold snail egg are macerated with a mixture of solvent acetone:methanol (1:8). The extract which had been vaporized, was tested its phytochemical compound with phytochemical screening test, the results of the phytochemical screening of the extract showed positive contain alkaloid, flavonoid, steroid, triterpenoid, saponin, and protein. The gold snail egg extract was then tested for its antioxidant activity quantitatively to obtain IC50 (Inhibitory Concentration) values from the extract using UV-Vis spectrophotometry at a wavelength (λmax) of 515 nm with vitamin C as a positive control. The results of spectrophotometric measurements show that gold snail egg extract has an IC50 value of 4,890 μg / ml and vitamin C has an IC50 value of 2,792 μg / ml. According to the result, it can be concluded that antioxidant activity of golden snail egg extract is lower than vitamin C but still potential as an antioxidant.